HISTOGENETIC ASPECTS OF PNEUMOFIBROSIS DURING CONIOTIC CHANGES IN KUZBASS MINERS - Олег Иванович Бондарев; Сергей Николаевич Филимонов (Медицина в Кузбассе)
Unfavorable working conditions of miners are a risk factor for the development of fibroplastic and neoplastic processes. The literature does not sufficiently cover the issues of fibrous transformation, histogenetic mechanisms of neoplastic processes in PC with subsequent neoplastic transitions of this tissue. Occupational dust pathology of respiratory organs in Kuzbass remains relevant due to its high prevalence among workers of the coal industry. Entering the body, various components of coal cause the development of pneumoconiotic fibrosis. New ideas about the histogenesis of fibrosis in recent years have shifted to the molecular level and appeal to the state of cellular receptors, the expression of some genes and the repression of others, the study of apoptosis processes, changes in cellular phenotype, as well as endothelial damage, which is the platform on which pathological processes occur in the future. The relevance of the problem. The Kemerovo region is the largest coal mining region in Russia, it is here that 58 % of the «black» fuel in the country is obtained. The Kuznetsk Coal Basin, the richest coal deposit in the world, is located on the territory of Kuzbass. Of the total reserves, 140 billion tons of coal are suitable for mining. At the same time, the coal industry is associated with difficult and dangerous working conditions, which are risk factors for occupational dust pathology of the respiratory organs. The aim of the study was to identify trigger morphological mechanisms of the development of oncological pathology in miners with signs of pneumofibrosis, based on pathomorphological, immunohistochemical studies of changes in the tissue of the airways during epithelial-mesenchymal transformation, apoptotic activity, proliferation of smooth muscle cells (MMC) and endothelial dysfunction. Materials and methods. Histological, morphometric and immunohistochemical studies of pulmonary histione obtained during 60 autopsy operations of a group of Kuzbass miners. All structural elements of lung tissue were studied. Immunohistochemical study was performed using monoclonal antibodies (proliferation marker Ki-67; oncogene of proapoptotic activity Vcl-2; endothelial function factors CD-31 and CD-34, macrophage factor NAM 56). The object of the study was histological, immunohistochemical and morphometric changes under microscopy, as well as interstitial correlations of these structures. Morphometric measurement of straight and curved linear dimensions of structures and their areas was carried out on an Olympus CX 31 microscope with a Nikon digital sight – Fi1 digital video camera. Morphometry was performed in structures without signs of traumatic effects. Results. Coal industry workers have pronounced changes in lung tissue, which manifest themselves in pronounced fibroplastic tissue transformation. These pathological changes cause the development of EMT with a likely transition to neoplastic tissue. The main source of fibrosis development in the lungs are activated myofibroblasts, the precursors of which can be as resident fibroblast-like cells. Dedifferentiated epithelial cells, MMCs, as well as endothelial cells can act as a source. Conclusions. The idea of fibrous tissue as a precursor of neoplastic processes in PC is only one facet of the histogenetic understanding of cellular transformation as a mechanism of the main pathological changes in pneumoconiosis. Intracellular changes occurring in PC should serve as a foundation for further in-depth study of complex pathogenetic aspects in medicine.